Attitudes of a Select Group of Illinois Quail Hunters - John L. Roseberry; William D. Klimstra (National Quail Symposium Proceedings, 2017)
During the past 3-4 decades major social, political, economic, and environmental changes have taken place in the United States that have greatly affected quail hunters, their quarry, and their sport. Against this backdrop, we examined the attitudes and perceptions of a select group of Illinois quail hunters from 1954 to 1989 regarding issues such as stocking, predator control, habitat management, and harvest regulations. During this time, hunters became increasingly cognizant of the importance of habitat and less inclined to demand unproductive practices such as stocking. Concerns about predators peaked in the 1970's. Hunters in the I980's tended to want more liberal hunting seasons than did their predecessors. Possible explanations and implications of these trends are discussed.
Keywords: attitudes; hunters; nothern bobwhite